Outcomes of an Equine Assisted Learning Curriculum to Support Well-Being of Medical Students and Residents. (July 2021) - Artz, Nicole L; Robbins, Jesse; Millman, Suzanne T
Objectives of this study were to evaluate an equine assisted learning (EAL) curriculum designed for medical students and resident physicians, and to determine impacts of the curriculum on participant perceptions of burnout and well-being. The EAL curriculum incorporated evidence-based skills and concepts to increase happiness and/or resilience. A pre/post intervention design was used, with 18 EAL participants receiving the curriculum within their month-long community based primary care clerkship elective, and 10 control (CTL) participants who did not receive the curriculum within their clerkship elective. Three waves of surveys tested participant responses before, immediately after, and 3 months after the intervention. Patient Health Questionnaire-4 (PHQ-4) screened for depression and anxiety, and Maslach Burnout Inventory- Human Services Survey for Medical Personnel (MBI) addressed burnout. Analysis of covariance evaluated differences between EAL and CTL groups. EAL participants rated the curriculum highly (9.2 on a 10-point scale). The evaluations were overwhelmingly positive with participants able to identify key concepts that were most helpful, how they would apply those concepts to patient care and interactions with colleagues, and how the horses added value to their learning experience. Significant positive effects of EAL on burnout were identified in terms of improved MBI personal achievement scores, as well as a trend towards improved well-being scores. There was also a trend ( P  < .08) towards PHQ-4 depression scores to be lower in EAL group at T3. In conclusion, this study is the first to provide AU: quantitative evidence of positive outcomes associated with an EAL curriculum designed to strengthen well-being in medical students and resident physicians.